Evaluation of an Integrated Household Refrigerator Evaporator with Two Eutectic Phase-Change Materials [Évaluation D Un Évaporateur de Réfrigérateur Domestique Intégré Avec Deux Matériaux À Changement de Phase Eutectiques] - Vasco-Calle, D; Jonathan Jesus-Cofre, T (Elsevier Ltd, 2018)
Domestic refrigerators are among the most energy-consuming appliances. In many countries, efforts have been undertaken to enhance the thermal efficiency of domestic refrigerators, and such improvements have been focused mainly on compressor operation and electronic control. The use of phase change materials (PCMs) in domestic refrigerators decreases the cycling period of the compressor and reduces internal temperature fluctuations. Two eutectic PCMs are thermally characterised (PLUSICE E-10 and 19.5 wt% NH4Cl). Their phase-change temperatures and latent heat values are determined, and their thermal conductivity and density are measured at 20 °C. The main goal of the present work is to study the behaviour of an integrated modified-evaporator of a household refrigerator with two different eutectic PCMs by performing standardised tests. In general, the experimental results help enhance our understanding and improve the operation of household refrigerators in terms of the power consumption and the inner temperature variation. © 2018 Elsevier Ltd and IIR